Branch prunning and chicken manure application to improve growth and yield of brocolli in lowland area - Okti Herliana; Yugi R Ahadiyat (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
The objective of this study was to determine the effect of branch pruning and chicken manure application on improving the growth and yield of broccoli in the lowland. The research was conducted in the dry land of Kutasari Village, Baturraden District, Banyumas Regency at 138 m above sea level. The research was arranged in a Factorial Randomized Complete Block Design (RCBD) with three replications consisting of two factors of chicken manure application (without chicken manure and with chicken manure at doses of 10 ton.ha-1 and 20 ton.ha-1) and branch pruning (without and with branch pruning of 25% and 50%). The pruning was performed when the plants initiated flowers. The observed data were analyzed with the F test and followed with Duncan's Multiple Range Test (DMRT) at a P>0.05. The branch pruning resulted in a significant effect on the number of leaves, leaf width, head weight, and head diameter. Meanwhile, the chicken manure application showed a significant effect on all of the observed variables. There was an interaction effect of branch pruning and chicken manure application on the leaf width, head weight, and head diameter. The best result was obtained by the combined treatment of 50% branch pruning and 20 ton.ha-1 chicken manure, resulting in the head weight of 1048.33 g.plant-1 and leaf width of 1705.41 cm2.